PERAMALAN VOLATILITAS DAN ESTIMASI VALUE AT RISK (VaR) SAHAM BLUE CHIP PADA SEKTOR PERBANKAN - JULIARINI, NI KADEK; SUMARJAYA, I WAYAN; SARI, KARTIKA (E-Jurnal Matematika, 2021)
Investment is an activity to invest an asset to obtain a greater profit. The investment there's in great demand by investors are stock investments. Based on market capitalization, stocks are classified into first-tier, second-tier, and third-tier stocks. Stocks that have the highest market capitalization are first-tier or blue-chip stocks. Blue-chip stocks are stocks that are classified as main shares on the listing board on the IDX. Before investing, it's important to know the level of investment risk in order to make the right investment decisions. The purpose of this study is to determine the risk of investing in blue-chip stocks namely BRI, BCA, and Bank Mandiri through volatility forecasting using the GARCH, EGARCH, or TGARCH models. The data used is the daily closing price of shares for the period of 25 May 2005 to 21 May 2021 which was obtained through the Yahoo Finance website. Based on the research results, it's known that Bank Mandiri has the highest investment risk and BCA has the lowest investment risk. Based on these results, it can be suggested that investors who like risk can choose to invest in Bank Mandiri shares, and those who don't like risk can invest in BCA shares.